Chronic historical drought legacy exacerbates tree mortality and crown dieback during acute heatwave-compounded drought. (3rd September 2018) - Matusick, George; Ruthrof, Katinka X; Kala, Jatin; Brouwers, Niels C; Breshears, David D; Hardy, Giles E St J
Abstract: Globally, combinations of drought and warming are driving widespread tree mortality and crown dieback. Yet thresholds triggering either tree mortality or crown dieback remain uncertain, particularly with respect to two issues: (i) the degree to which heat waves, as an acute stress, can trigger mortality, and (ii) the degree to which chronic historical drought can have legacy effects on these processes. Using forest study sites in southwestern Australia that experienced dieback associated with a short-term drought with a heatwave (heatwave-compounded drought) in 2011 and span a gradient in long-term precipitation (LTP) change, we examined the potential for chronic historical drought to amplify tree mortality or crown dieback during a heatwave-compounded drought event for the dominant overstory species Eucalyptus marginata and Corymbia calophylla . We show pronounced legacy effects associated with chronically reduced LTP (1951–1980 versus 1981–2010) at the tree level in both study species. When comparing areas experiencing 7.0% and 11.5% decline in LTP, the probability of tree mortality increased from low (<0.10) to high (>0.55) in both species, and probability of crown dieback increased from high (0.74) to nearly complete (0.96) in E. marginata . Results from beta regression analysis at the stand-level confirmed tree-level results, illustrating a significant inverse relationship between LTP reduction and either tree mortality ( F  = 10.39, P  = 0.0073) or dieback ( F  = 54.72, P  < 0.0001). Our findings quantify chronic climate legacy effects during a well-documented tree mortality and crown dieback event that is specifically associated with an heatwave-compounded drought. Our results highlight how insights into both acute heatwave-compounded drought effects and chronic drought legacies need to be integrated into assessments of how drought and warming together trigger broad-scale tree mortality and crown dieback events.